Identification of antagonistic Streptomyces strains isolated from Algerian Saharan soils and their plant growth promoting properties - Lamia AOUAR; INAS BOUKELLOUL; ABDERRAHMANE BENADJILA (Society for Indonesian Biodiversity, 2020)
Abstract. Aouar L, Boukelloul I, Benadjila A. 2020. Identification of antagonistic Streptomyces strains isolated from Algerian Saharan soils and their plant growth promoting properties. Biodiversitas 21: 5672-5683. To produce new bioactive substances of agricultural interest, extreme ecosystems can be a source of unexplored microorganisms. Accordingly, in this study, twenty-two actinobacteria strains were obtained from rhizospheric arid soils of palm groves collected from Biskra and El Oued in the Algerian Sahara. All isolates were examined for the in vitro antifungal potential towards phytopathogenic fungi: Aspergillus flavus, Verticillium dahlia, Rhizoctonia solani, Botrytis cinerea and Fusarium oxysporum as well as for their antibacterial property toward phytopathogenic bacteria: Streptomyces scabiei, Pectobacterium carotovorum and Agrobacterium tumefaciens. The three isolates (13%) that inhibited at least five pathogens were then selected, identified and assessed for their attributes to produce indole-3-acetic acid (IAA) and siderophores, to solubilize phosphate, and to antagonize Streptomyces scabiei in vivo. According to phylogenetic analysis performed with 16S rDNA sequence, chemotaxonomy and phenotypic characteristics, the strain SO1, which inhibited all tested pathogens, was assigned to Streptomyces flaveus. While, strains SO2 and SB1 were affiliated to Streptomyces enissocaesilis and Streptomyces albidoflavus, respectively. All strains produced IAA but only SO1 and SB1 were able to elaborate siderophores catecholate-type. Two strains SO1 and SO2 exhibited a capacity to solubilize phosphate and SO1 was able to suppress the pathogenic effect of Streptomyces scabiei on radish seedlings. The findings indicate that SO1 strain may reveal the potential for use as a biocontrol agent and plant growth promoter.